Enteral nutritional support for an elderly critically ill patient with gastroesophageal reflux disease and situs inversus totalis: a case report - Chen, Yuanyuan; Ma, MengLin; Huang, Xiaoqing; Wan, Jia; Huang, Haiyan (Frontiers in Nutrition, 2025)
Herein, we present a case of serious protein-energy malnutrition in an elderly critically ill patient with situs inversus totalis. It was difficult to implement enteral nutrition in this patient for more than 2 months of hospitalisation in another hospital, and we applied electromagnetic navigation guidance to implement enteral nutrition after successful placement of nasojejunal tubes. We reviewed the management of enteral nutrition support.